Case report: Reassessing guidelines for safe resumption of diving after spinal decompression sickness: insights from a challenging case - Druelle, Arnaud; Blatteau, Jean-Eric; Daubresse Duchadeuil, Lucile; Morin, Jean; Roffi, Romain; Dufresne, Pierre-Louis; Lehot, Henri; Castagna, Olivier (Frontiers in Medicine, 2024)
(DCS) often aspire to return to their diving activities. Traditionally, it is recommended to observe a waiting period of several months before contemplating a return to unrestricted diving, particularly when clinical symptoms are absent, spinal cord Magnetic Resonance Imaging shows no anomalies, and the evaluation for Patent Foramen Ovale (PFO) returns negative results.Methods. This article presents a compelling case study involving a 51-year-old recreational scuba diver who encountered two episodes of spinal decompression illness within a two-year timeframe. Notably, the search for a PFO produced negative results. The primary objective of this article is to underscore the critical importance of a meticulously planned approach to resuming diving after DCS incidents, emphasizing the potential for recurrence and the essential preventive measures.We delve into the intricate decision-making process for returning to diving, emphasizing the significance of clinical evaluations, PFO assessments, spinal cord Magnetic Resonance Imaging, and the absence of clinical symptoms. By recognizing the risk of recurrence and the need for proactive prevention measures, we provide recommendations for both medical professionals and divers, with the ultimate goal of enhancing safety and informed decision-making within the diving community.